Sosialisasi Nilai-Nilai Agama pada Anak dalam Keluarga Muslim - Djazuli Djazuli (UIN Maulana Malik Ibrahim Malang, 2004)
Religion generally considers that family is an eternal and sacred institution. The institution is regarded as part of the divine nature for every man, whether male or female. In sociological perspective, religion is set on a very basic area. Because religion is the principle of all principles. This paper explains the socialization of religious values that shape the personality of child. How religious values color the interaction in Muslim families between children and parents. Through the explorative approach, this study found that the value of religion can be reflected from various aspects such as structuring the condition of the house, the establishment of an environment that builds the character of the child and the effort to socialize the religious values from an early age. The socialization is reflected through the life cycle of Muslims and the pattern of formal and informal education of children. Agama pada umumnya memandang bahwa lembaga keluarga merupakan lembaga yang abadi dan suci. Lembaga tersebut dianggap sebagai bagian dari kodrat Ilahi bagi setiap manusia baik laki-laki ataupun perempuan. Dalam perspektif sosiologis, religi ditempatkan pada kawasan yang sangat mendasar. Karena religi dalam pengertian agama merupakan prinsip dari segala prinsip dan azas dari segala azas. Tulisan ini menjelaskan sosialisasi nilai agama yang membentuk kepribadian anak. Bagaimana nilai agama mewarnai interaksi dalam keluarga muslim antara anak dan orang tua. Melalui pendekatan eksploratif, kajian ini menemukan bahwa nilai agama dapat direfleksikan dari berbagai aspek seperti penataan kondisi rumah, pembentukan lingkungan yang membangun karakter anak dan upaya sosialisasi nilai agama sejak dini. Sosialisasi tersebut tercermin melalui siklus kehidupan muslim dan pola pendidikan anak baik formal maupun informal.